Active vitamin D is cardioprotective in experimental uraemia but not in children with CKD Stages 3-5 - Schön, Anne; Leifheit-Nestler, Maren; Deppe, Jennifer; Fischer, Dagmar-Christiane; Bayazit, Aysun K; Obrycki, Lukasz; Canpolat, Nur; Bulut, Ipek Kaplan; Azukaitis, Karolis; Yilmaz, Alev; Mir, Sevgi; Yalçinkaya, Fatma Fatos; et al. (Nephrology, dialysis, transplantation, 2021)
Uraemic cardiac remodelling is associated with vitamin D and Klotho deficiency, elevated fibroblast growth factor 23 (FGF23) and activation of the renin-angiotensin system (RAS). The cardioprotective properties of active vitamin D analogues in this setting are unclear. In rats with 5/6 nephrectomy (5/6Nx) treated with calcitriol, the cardiac phenotype and local RAS activation were investigated compared with controls. A nested case-control study was performed within the Cardiovascular Comorbidity in Children with Chronic Kidney Disease (4C) study, including children with chronic kidney disease (CKD) Stages 3-5 [estimated glomerular filtration rate (eGFR) 25 mL/min/1.73 m2] treated with and without active vitamin D. Echocardiograms, plasma FGF23 and soluble Klotho (sKlotho) were assessed at baseline and after 9 months.In rats with 5/6Nx, left ventricular (LV) hypertrophy, LV fibrosis and upregulated cardiac RAS were dose-dependently attenuated by calcitriol. Calcitriol further stimulated FGF23 synthesis in bone but not in the heart, and normalized suppressed renal Klotho expression. In the 4C study cohort, treatment over a mean period of 9 months with active vitamin D was associated with increased FGF23 and phosphate and decreased sKlotho and eGFR compared with vitamin D naïve controls, whereas LV mass index did not differ between groups.Active vitamin D ameliorates cardiac remodelling and normalizes renal Klotho expression in 5/6Nx rats but does not improve the cardiac phenotype in children with CKD Stages 3-5. This discrepancy may be due to further enhancement of circulating FGF23 and faster progression of CKD associated with reduced sKlotho and higher serum phosphate in vitamin D-treated patients.
Advance access publication 30 November 2020
Gesehen am 13.07.2021